Targeted delivery of liposomal chemoimmunotherapy for cancer treatment - Liu, Yusheng; Han, Joonsu; Bo, Yang; Bhatta, Rimsha; Wang, Hua (Frontiers in Immunology, 2022)
Chemo-immunotherapy that utilizes the immunomodulatory effect of chemotherapeutics has shown great promise for treating poorly-immunogenic solid tumors. However, there remains significant room for improving the synergy between chemotherapy and immunotherapy, including the efficient, concurrent delivery of chemotherapeutics and immunomodulators into tumors. Here we report the use of metabolic glycan labeling to facilitate cancer-targeted delivery of liposomal chemo-immunotherapy. 4T1 triple negative breast cancer cells can be metabolically labeled with azido groups, for subsequent targeted conjugation of dibenzocycoloctyne (DBCO)-bearing liposomes loaded with doxorubicin and R837 adjuvant via efficient click chemistry. The encased doxorubicin can induce the immunogenic death of cancer cells and upregulate the expression of CD47 and calreticulin on the surface of cancer cells, while R837 can activate dendritic cells for enhanced processing and presentation of tumor antigens. Targeted delivery of liposomes encapsulating doxorubicin and R837 to 4T1 tumors, enabled by metabolic glycan labeling and click chemistry, showed the promise to reshape the immunosuppressive tumor microenvironment of solid tumors. This cancer-targetable liposomal chemo-immunotherapy could provide a new approach to improving conventional chemotherapy.